Evangelical Sunday School and Character Building: A Study of Christian Education for Children of Pre-adolescent Level - Sopakua, Samel; Leinatta, Meilany S.; Matital, Noni; Saimima, Alexandra M. (Didache: Journal of Christian Education, 2024)
SMTPI is a form of formal church education that also serves as a platform for Christian Religious Education services for children. At SMTPI, children have the opportunity to learn and receive various teachings. One of the primary goals of Christian Religious Education (CRE) at SMTPI is character building, a process where children undergo changes in inner attitudes that influence their thoughts, behavior, character, and overall human nature. The purpose of this study is to identify the factors that influence the character-building of SMTPI children at the pre-adolescent level and to evaluate how SMTPI contributes to their character-building, viewed from the perspective of CRE. Based on analysis conducted through observation, interviews, and literature review, two key factors are identified as influencing children’s character building: internal and external factors. Additionally, SMTPI contributes significantly to character building by employing various creative and innovative teaching methods in its learning process. These methods help reduce children’s boredom while studying, making it easier for them to grasp the meanings and messages conveyed by caregivers. This approach ensures that children experience a process of character building that aligns with Christian values, fostering the formation of better character traits by Christian principles.